2015
DOI: 10.26753/jikk.v11i3.110
|View full text |Cite
|
Sign up to set email alerts
|

Gambaran Peran Kader Dalam Pelaksanaan Program Perencanaan Persalinan Dan Pencegahan Komplikasi (P4k) Di Wilayah Kerja Puskesmas Padureso Kabupaten Kebumen

Abstract: Mortality and morbidity is a big problem in a developing  country such as Indonesia. Minister of Health in 2007 planned a program of labor Planning and Complications Prevention (Indonesian=P4K) by using stickers as efforts to accelerate the decline in infant mortality rate (IMR) and maternal mortality rate (MMR). By implementation of this Program, there should be a good role of midwives, kader, religious leaders, community leaders, husbands, pregnant women and families.This study is to find out the overview of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 0 publications
0
3
0
3
Order By: Relevance
“…Stunting merupakan gangguan pada pertumbuhan linear yang menyebabkan seorang anak memiliki panjang/tinggi badan tidak sesuai usianya (berada dibawah -2SD). Kondisi ini terjadi akibat kekurangan gizi kronis dan infeksi berulang pada 1000 hari pertama kehidupan (HPK) (Kusuma et al, 2022).…”
Section: Pendahuluanunclassified
See 1 more Smart Citation
“…Stunting merupakan gangguan pada pertumbuhan linear yang menyebabkan seorang anak memiliki panjang/tinggi badan tidak sesuai usianya (berada dibawah -2SD). Kondisi ini terjadi akibat kekurangan gizi kronis dan infeksi berulang pada 1000 hari pertama kehidupan (HPK) (Kusuma et al, 2022).…”
Section: Pendahuluanunclassified
“…Penyebab secara tidak langsungnya yaitu faktor ketahanan pangan keluarga, pola asuh, pelayanan kesehatan dan kesehatan lingkungan yang tidak memadai mencakup air dan sanitasi. Penyebab dasar terjadinya stunting dihubungkan dengan pendidikan, kemiskinan, sosial budaya, kebijakan pemerintah dan politik (Kusuma et al, 2022).…”
Section: Pendahuluanunclassified
“…The P4K program focuses on community empowerment by involving various community elements to prevent maternal mortality. Community support such as family, cadres, community leaders and religious leaders is important to support maternal health (Kementrian Kesehatan R1, 2014; Kusumastuti, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Cadres themselves are local communities who are selected, work voluntarily (Kusumastuti, 2015). The research conducted by Pangestu (2017) found that cadres have 4 important roles, first is MCH surveillance, reduction in maternal mortality, infant mortality, and children mortality, increasing coverage of pregnancy check-up, early detection of pregnancy with abnormalities, and monitoring of pregnancy, and the role of increasing POSYANDU participation and early detection of children's growth issues.…”
Section: Introductionmentioning
confidence: 99%
“…Pencegahan Komplikasi), hal ini sesuai dengan penelitian Triayu pawestri (2010). [15] Sarana dan prasarana terkait pelaksanaan P4K (Kusumawati, 2015). [17] e-ISSN: 2541-4542…”
unclassified